Impact of Deuteration on the Assembly Kinetics of Transthyretin Monitored by Native Mass Spectrometry and Implications for Amyloidoses. (17th June 2016) - Yee, Ai Woon; Moulin, Martine; Breteau, Nina; Haertlein, Michael; Mitchell, Edward P.; Cooper, Jonathan B.; Boeri Erba, Elisabetta; Forsyth, V. Trevor
Abstract: It is well established that the formation of transthyretin (TTR) amyloid fibrils is linked to the destabilization and dissociation of its tetrameric structure into insoluble aggregates. Isotope labeling is used for the study of TTR by NMR, neutron diffraction, and mass spectrometry (MS). Here MS, thioflavin T fluorescence, and crystallographic data demonstrate that while the X‐ray structures of unlabeled and deuterium‐labeled TTR are essentially identical, subunit exchange kinetics and amyloid formation are accelerated for the deuterated protein. However, a slower subunit exchange is noted in deuterated solvent, reflecting the poorer solubility of non‐polar protein side chains in such an environment. These observations are important for the interpretation of kinetic studies involving deuteration. The destabilizing effects of TTR deuteration are rather similar in character to those observed for aggressive mutations of TTR such as L55P (associated with familial amyloid polyneuropathy).